2013
DOI: 10.1152/ajpheart.00606.2012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary flaxseed on atherosclerotic plaque regression

Abstract: Francis AA, Deniset JF, Austria JA, LaValleé RK, Maddaford GG, Hedley TE, Dibrov E, Pierce GN. Effects of dietary flaxseed on atherosclerotic plaque regression. Am J Physiol Heart Circ Physiol 304: H1743-H1751, 2013. First published April 12, 2013 doi:10.1152/ajpheart.00606.2012.-Dietary flaxseed can retard the progression of atherosclerotic plaques. However, it remains unclear whether these antiatherogenic effects extend to plaque regression. In the present study, the therapeutic potential of dietary flaxsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 50 publications
1
26
0
1
Order By: Relevance
“…Lignins may be responsible for the reducing lipid concentrations. Their metabolites in the organism can bind to bile acids and other chemical compounds such as cholesterol, retarding or diminishing the absorption of these compounds [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignins may be responsible for the reducing lipid concentrations. Their metabolites in the organism can bind to bile acids and other chemical compounds such as cholesterol, retarding or diminishing the absorption of these compounds [34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, because its omega fatty acids are associated with lignins and vitamins, linseed is considered a functional food with potential antiatherogenic effects [35,36]. Kaithwas et al [37] demonstrated that Linum usitatissimum fixed oil possesses anti-inflammatory, analgesic and antipyretic activities.…”
Section: Discussionmentioning
confidence: 99%
“…Flaxseed is one of the richest sources of alpha-linolenic acid and lignans, both of which can reduce total cholesterol and LDLcholesterol [12][13][14][15] . In addition to their cholesterol-lowering effect, fl axseed 16,18 and oat 19 have been reported to cause a regression of the atherosclerosis process in animals.…”
Section: Methodsmentioning
confidence: 99%
“…There are ample of research evidences that have utilized nutritional interventions to induce plaque regression, these studies have all prematurely initiated their interventions before there is clear evidence of cessation of plaque growth [12]. It is evident that the anti-atherosclerotic effects of drugs based on flaxseed α-linolenic acid and lignans are not inferior to the effects of such drugs as statins and calcium antagonists.…”
Section: Future Perspectivementioning
confidence: 99%